Virtualization of home networking equipment on 5G cloud - Vieira, Tiago André Borges (2019)
In order to increase flexibility and agility in the way that network operators deliver their services, the virtualization of the Customer Premises Equipments (CPE) has been being proposed. This dissertation extends such approach and proposes a solution that enables the deployment of CPEs’ network functions in a chain of containerized virtual network functions (VNFs) creating virtual CPE instances (vCPEs) organized in clusters. Through Software Defined Networks (SDN) and Network Function Virtualization (NFV) mechanisms, vCPEs can be migrated among clusters ensuring the balancing of its resources, or to fulfill the requirements of a specific data transmission. A proof of concept prototype was tested with a transmission of a video in Full and Ultra High-Definition, showing none impact in the quality of experience of end-users when vCPE migration is taking place.